Criminal Punishment Without Civil Rights: The Criminal Proceeds and Instruments Bill’s Punitive Civil Sanctions - Wright, Peter (Victoria University of Wellington Law Review, 2006)
This article critiques the Criminal Proceeds and Instruments Bill 2005 which introduces a civil forfeiture regime for the proceeds of serious criminal offending. By using a civil forfeiture regime, many of the protections normally granted to criminal defendants are not available, which makes successful action by the State easier. This article argues that the Bill’s civil forfeiture regime risks seriously abrogating individuals’ rights, including those arising from the requirement for proof beyond a reasonable doubt and the prohibitions on double jeopardy and retrospective punishment. The article concludes that the confiscation of criminals’ assets should take place within the criminal justice system to ensure that there are proper protections for defendants.